Epilepsy Journey: A proof of concept trial of a Web‐based executive functioning intervention for adolescents with epilepsy. (19th August 2019) - Modi, Avani C.; Mara, Constance A.; Schmidt, Matthew; Smith, Aimee W.; Turnier, Luke; Glaser, Noah; Wade, Shari L.
Summary: Objective: To examine the preliminary feasibility and acceptability of a Web‐based program, Epilepsy Journey, to improve executive function behaviors in adolescents with epilepsy. Methods: We conducted a proof of concept single‐arm pilot trial of Epilepsy Journey with 31 adolescents (average age = 15.3 ± 1.3 years) who had an epilepsy diagnosis and executive function (EF) deficits on the caregiver‐report version of the Behavior Rating Inventory of Executive Function (BRIEF). Epilepsy Journey coupled a gamified problem‐solving website comprised of 10 learning modules targeting EF deficits (eg, working memory, organization, problem‐solving) with Skype sessions with a trained therapist. Outcomes included feasibility (attrition, sessions completed) and acceptability (satisfaction ratings). Exploratory analyses examined changes in caregiver‐, self‐, and teacher‐reported BRIEF scores from baseline to posttreatment and at 2‐ and 5‐month follow‐ups. Results: Seventy‐nine percent of participants completed the program. Satisfaction was high, with 97% of caregivers and adolescents rating the program as helpful and indicating they would recommend it to others. Caregivers and adolescents reported global improvements on the BRIEF, with caregivers reporting significant improvements on all BRIEF subscales. EF symptoms rebounded slightly between the 2‐ and 5‐month follow‐ups for some of the self‐ and caregiver‐reported BRIEF scales. Notably, clinically meaningful improvements (eg, clinical/subclinical to normative levels) were reported for several caregiver‐reported BRIEF subscales, including the Global Executive Composite (62% to 33‐34%) and Metacognitive Index (74% to 41‐42%) from baseline to 2‐ and 5‐month follow‐up. Significance: Findings suggest that a Web‐based problem‐solving intervention tailored to EF deficits for adolescents with epilepsy is both feasible and acceptable and may contribute to improvements in EF behaviors across domains.